Constraints of S–Pb–Sr Isotope Compositions and Rb–Sr Isotopic Age on the Origin of the Laoyingqing Noncarbonate-Hosted Pb–Zn Deposit in the Kunyang Group, SW China. (8th February 2021) - Gong, Hongsheng; Han, Runsheng; Wu, Peng; Chen, Gang; Li, Lingjie
Abstract : The Laoyingqing Pb–Zn deposit is located on the southwestern margin of the Yangtze block and on the east side of the Xiaojiang deep fault in the Sichuan–Yunnan–Guizhou Pb–Zn metallogenic triangle area (SYGT). This deposit was first discovered in the silty and carbonaceous slate of the Middle Proterozoic Kunyang Group that is structurally controlled by thrust faults and anticlines. This study is aimed at investigating whether the Laoyingqing deposit has the same ore-forming age and type as other Pb–Zn deposits related to the Pb–Zn metallogenic system and prospecting prediction of the deep and peripheral areas of the deposits in the SYGT. Based on the sphalerite Rb–Sr age dating and S–Sr–Pb isotopic composition analysis of the Laoyingqing Pb–Zn deposit, the following results were obtained. First, the Rb–Sr isochron age of sphalerite is 209.8 ± 5.2 million years (Ma), consistent with the ages of most Pb–Zn deposits in the SYGT (approximately 200Ma), thereby potentially indicating that these Pb–Zn deposits may have been formed synchronously during the late Indosinian orogeny. Second, the Pb isotopic compositions of sulfides show a linear trend on the average crustal Pb evolution curve in 207 Pb/ 204 Pb vs. 206 Pb/ 204 Pb plot. In addition, Pb isotopic ratios were consistent with the age-corrected Pb isotopic ratios of basement rocks, consequently suggesting that the source of mixed crustal Pb is mainly derived from basement rocks. Combined with the initial 87 Sr/ 86 Sr ratios of sphalerite between the ( 87 Sr/ 86 Sr)200Ma value of the basement rocks and that of the Upper Sinian–Permian carbonates, it can be concluded that the ore-forming metals were mainly derived from basement rocks. Third, sulfur isotopic composition of sphalerite from the Laoyingqing deposits shows δ 34 SCDT values that range mainly from -2.62‰ to 1.42‰, which is evidently lower than the δ 34 SCDT values of sulfides (8–20‰) from other Pb–Zn deposits in the SYGT. This can be interpreted as a result of mixing with reduced S that was mainly derived from the thermochemically reduced S in the overlying strata and a small amount of reduced S produced by the pyrolysis of S-containing organic matter. We conclude that the Laoyingqing deposit and most of the Pb–Zn deposits in the SYGT are Mississippi Valley-type deposits, thereby providing new ideas for investigating the deep and peripheral areas of Pb–Zn deposits.